Placebo effect: influence on repeated intermittent sprint performance on consecutive days - Tolusso, D. V.; Laurent, C. M.; Fullenkamp, A. M.; Tobar, D. A. (The Journal of Strength and Conditioning Research, 2015)
Despite the available literature addressing the placebo effect's role in mediating human performance, there is a paucity of research addressing the possibility of a placebo effect both within and between bouts of repeated sprint performance on consecutive days. Therefore, the purpose of this study was to determine whether the administration of a placebo influences recovery during sessions of intermittent sprinting. Ten subjects performed 4 repeated sprint tests under 2 different conditions; 2 while being administered a control beverage separated by 24 hours of recovery and the other 2 with a placebo beverage separated by 24 hours of recovery. Before each sprint test, subjects provided perceived recovery status (PRS). Ratings of perceived exertion were recorded within 5 seconds after each sprint. After each repeated sprint protocol, subjects were asked to provide a rating of perceived exertion (RPE), rate their pain, and provided a blood lactate sample. Power was recorded throughout each session from a nonmotorized treadmill to analyze changes in sprinting performance. Repeated-measures analysis of variance was used to determine significant differences in peak and mean power, PRS, RPE, pain, and blood lactate. The placebo trial produced significantly higher peak (p < 0.001) and mean power (p = 0.002) vs. the control in later sprints absent of any other significant difference in metabolic or perceptual strain (p > 0.05). In conclusion, it seems that the administration of a placebo can attenuate the decline in performance as fatigue increases during repeated sprinting bouts.